ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA PT. BANJAR OPTIK - Tanza, Donavan; Rusdi, Zyad (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
The purpose of this system analysis and design is to find the problems and weaknesses that exist in the company and design a new computer based information system to support business operation of the company. The old system in the company has various problems such as data recording errors, calculation errors, difficulty in accessing data, data loss, and low quality of reports for decision making. The methodology used in this system analysis and design is SDLC (System Development Life Cycle) which consists of planning, analysis, design, and implementation phase. This new system is analysed and designed to manage processes in various divisions with computerized data management and integrated database. Key words Computerized system, Database, System analysis and design. Information system.